Methods of Correct Placement of Counters and Information Boards in Historical Monuments (Journal of Architectural Design, 2022)
The article reveals the problem of "visual noise" in the architectural appearance of the building caused by irregular placement of information signs. Requirements regulating the installation and maintenance of such information stands, as well as the main provisions of legal documents regulating the field are analyzed. Today, foreign experiments on preservation of the appearance of architectural monuments have been studied. The article contains recommendations on the correct placement of counters and information boards currently installed in architectural monuments.